2016
DOI: 10.1111/mmi.13431
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of two toxin–antitoxin systems in Campylobacter jejuni

Abstract: Toxin-antitoxin (TA) systems are widely distributed in bacteria and play an important role in maintaining plasmid stability. The leading foodborne pathogen, Campylobacter jejuni, can carry multiple plasmids associated with antibiotic resistance or virulence. Previously a virulence plasmid named pVir was identified in C. jejuni 81-176 and IA3902, but determining the role of pVir in pathogenesis has been hampered because the plasmid cannot be cured. In this study, we report the identification of two TA systems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Our large genome analysis revealed that this physical genomic link between TA pairs and CRISPR arrays can be extended to the majority of sequenced C. difficile strains. Initially, TA systems were shown to be important for maintenance of plasmids through a post-segregation killing mechanism ( 20 , 21 , 84 ). The role of numerous chromosomal TA systems remains largely enigmatic, even though their possible implication in stabilization of chromosomal regions has been emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Our large genome analysis revealed that this physical genomic link between TA pairs and CRISPR arrays can be extended to the majority of sequenced C. difficile strains. Initially, TA systems were shown to be important for maintenance of plasmids through a post-segregation killing mechanism ( 20 , 21 , 84 ). The role of numerous chromosomal TA systems remains largely enigmatic, even though their possible implication in stabilization of chromosomal regions has been emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…CjrA/CjpT (type I) and VirA/VirT (type II) TA systems were identified in Campylobacter spp. (377). These systems were encoded by the pVir plasmid, which is involved in virulence and natural transformation.…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 99%
“…These systems were encoded by the pVir plasmid, which is involved in virulence and natural transformation. VirT belongs to the RelE family, one of the best-studied TA systems (374,377).…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 99%
“…Campylobacter genomes generally lack homologs of prototypical TA systems ( Shao et al, 2011 ). To date, only two TA systems (both located on a plasmid in C. jejuni ) have been described ( Shen et al, 2016 ). Given the general importance of TA systems in bacteria we asked whether the multiple fic genes in C. fetus fulfill this important role.…”
Section: Introductionmentioning
confidence: 99%